2018
DOI: 10.1186/s13018-018-0938-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of COMP and CS846 biomarkers in experimental rat osteoarthritis: a potential approach for assessment and diagnosis of osteoarthritis

Abstract: BackgroundTo comprehensively evaluate the diagnostic value of serum cartilage oligomeric matrix protein (COMP) and chondroitin sulfate 846 epitope (CS846) biomarkers in osteoarthritis (OA), longitudinal and combined measurement of serum COMP and CS846 were performed at different stages in the pathological process of OA in a rat model of anterior cruciate ligament transection (ACLT).MethodsSixty male Sprague-Dawley rats were randomly divided into two groups, including a model group (n = 30) and a control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…However, there was no statistically significant difference in the PROM scores between the ASCs and model groups, and MRI and SEM still showed obvious cartilage damage in the ASCs group. In addition, the increase in serous COMP was prevented by all three therapies, which was consistent with the results of previous investigations showing a positive relationship between the level of COMP and the KOA grade score [72]. Among the three treatment groups, the acupotomy group had the best inhibition effect on serous COMP increase, followed by the combination therapy, both of which were significantly better than the ASCs group.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was no statistically significant difference in the PROM scores between the ASCs and model groups, and MRI and SEM still showed obvious cartilage damage in the ASCs group. In addition, the increase in serous COMP was prevented by all three therapies, which was consistent with the results of previous investigations showing a positive relationship between the level of COMP and the KOA grade score [72]. Among the three treatment groups, the acupotomy group had the best inhibition effect on serous COMP increase, followed by the combination therapy, both of which were significantly better than the ASCs group.…”
Section: Discussionsupporting
confidence: 90%
“…Rats receiving a sham operation served as the control. The rat OA model was produced by ACLT, as described previously 21 23 . In OA model groups, the rats received vehicle injections of 0.9% normal saline and a sham LIPUS stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…COMP is a tissue-speci c protein that binds to type II collagen network and plays a role in collagen bundles and collagen network structure [23,43]. CS 846 epitope is a chondroitin sulfate synthetic biomarker and inseparable from the degree of joint injury in patients with OA [24,44]. Our study found that the concentration of CTX-II, COMP and CS 846 in the SF is higher than that in the serum.…”
Section: Paragraphmentioning
confidence: 62%